Protagonism of students who develop activities With a technology center (Revista Contexto & Educação, 2024)
Technological advances have exerted a significant influence on several areas of knowledge. However, in the area of education, the use of traditional and obsolete instructional methodologies still persists. This study seeks to explore constructivist alternatives allied to technology in order to encourage student protagonism. Through the implementation of workshops focused on technology topics in a maker laboratory, with high school participants, the aim is to promote activities that favor the cognitive development of students. Meetings planned at different times made it possible to conduct discussions that established connections between the students' perceptions, constructivist theories and the principles of the maker culture, with the aim of encouraging the adoption of the role of protagonist. The results show the effectiveness of the constructivist approach and the maker environment in promoting the protagonism of learners. Such an approach stimulated student engagement, boosting the development of scientific thinking, cognitive skills and the desire to share knowledge.
Keywords: construtivism; maker culture; educational computing